(untitled) (Asian Journal of Social Science Studies, 2016)
In this paper, by using China’s urban population data from 1990 to 2010 and double logarithmic regression model to test China’s urban scale and urban rank through Zipf law, we found that China’s urban scale distribution is relatively balanced, virtually conforming to Zipf’s law. Researching and analyzing urban scale distribution of China’s every province’s, we also found that the urban scale distributions of China’s all provinces are relatively complicated and they are not even close to 1. The increase of Zipf index means that urban scale distribution is transiting from primacy degree distribution to ideal Zipf distribution. Further analyzing and categorizing every province’s Zipf index, we can conclude that China’s urban scale distribution can be categorized four mainly: achieved ideal Zipf law; approaching to ideal Zipf distribution; The transition state from the primacy degree distribution to the Zipf law distribution; typical primacy degree distribution.